Wave Propagation in Nanostructures Nonlocal Continuum Mechanics Formulations - Gopalakrishnan, Srinivasan; Narendar, Saggam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Wave Propagation in Nanostructures describes the fundamental and advanced concepts of waves propagating in structures that have dimensions of the order of nanometers. The book is fundamentally based on non-local elasticity theory, which includes scale effects in the continuum model. The book predominantly addresses wave behavior in carbon nanotubes and graphene structures, although the methods of analysis provided in this text are equally applicable to other nanostructures. The book takes the reader from the fundamentals of wave propagation in nanotubes to more advanced topics such as rotating nanotubes, coupled nanotubes, and nanotubes with magnetic field and surface effects. The first few chapters cover the basics of wave propagation, different modeling schemes for nanostructures and introduce non-local elasticity theories, which form the building blocks for understanding the material provided in later chapters. A number of interesting examples are provided to illustrate the important features of wave behavior in these low dimensional structures.
Introduction to Nanostructures -- Introductory Concepts of Wave Propagation Analysis in Structures -- Various Modeling Techniques for Nanostructures -- Theory of Nonlocal Elasticity -- Material Property and Nonlocal Scale Parameter Estimation for SWCNTs -- Wave Propagation in 1D-Nanostructures: Nanorods -- Wave Propagation in 1D-Nanostructures: Nanobeams -- Wave Propagation in Multi-Walled Carbon Nanotubes -- Wave Propagation in Coupled 1D-Nanosystems -- Wave Propagation in 2D-Nanostructures -- Wave Propagation in Nanoshells.
Keywords: Physics; Mechanics; Materials; Engineering; Nanotechnology; Physics; Nanoscale Science and Technology; Continuum Mechanics and Mechanics of Materials; Mechanics; Nanotechnology; Nanotechnology and Microengineering